VIEWS ON RESTRICTIVE MEASURES AMONG BRAZILIAN LAWYERS DURING THE COVID-19 OUTBREAK - Fabio de Sá e Silva (Brazilian Journal of Empirical Legal Studies, 2022)
COVID-19 has had deep impacts on the lives of individuals, organizations, and polities around the globe. Legal professionals and institutions were not absent from this story. Governments adopted different approaches to deal with the pandemic, which – at a time when social relations have become ever more judicialized – inevitably triggered legal disputes. Central to these disputes were restrictive measures such as lockdown for non-essential businesses, shelter-in-place and stay-at-home orders for communities, and compulsory quarantine for infected individuals. These disputes were further entangled with political conflict and polarization, as the case of Brazil under President Jair Bolsonaro well exemplifies. Against such backdrop, this article investigates: Did Brazilian legal professionals view those restrictive measures and the power of government entities to enact them to be consistent with ‘the law’? What explains variation in their views? By exploring data from rapid research carried out during the pandemic outbreak in Brazil, this article points to the role of variables such as pandemic understandings and experiences, political orientation and attitudes, and the nexus between legal knowledge and the State in shaping the attitude of such population. The implications to studies on legal professionals, pandemics, and the rule of law in Brazil and beyond are discussed.